DROUGHT TOLERANCE, PHOSPHORUS EFFICIENCY AND YIELD CHARACTERS OF UPLAND RICE LINES - Ahadiyat, Yugi R.; Hidayat, Ponendi; Susanto, Untung (Emirates Journal of Food and Agriculture, 2013)
Objective of this study was to evaluate the characters of drought tolerance, P efficiency and yield of some upland rice lines based on shoot biomass, P accumulation and grain yield. Nine lines of upland rice [viz. aromatic upland rice (Unsoed: G9, G13, G19, G35, G39), upland rice from Rice Research Center Sukamandi (IR-80340-23-B-B-1-B-B, IR 75885-25-1-3-B-5-1-2-B-B, IR 75885-26-2-3-B-18-B-2-1-B), upland rice from University of Mataram (Unram 1E)], four P doses per pot [viz. 0, 0.20, 0.40 and 0.55 kg P2O5] and soil water availability [viz. field capacity (FC) (-10 kPa), 50% FC (-24 kPa), 75% FC (-17 kPa) and 25% FC (-30 kPa) were tested. The study was arranged in randomized complete block design with three replicates. The result showed that upland rice lines of IR 75885-26-2-3-B-18-B-2-1-B, Unsoed G9 and Unsoed G19 resulted higher in grain yield under drought condition than others. Yet, Unram 1E and Unsoed G13 had potency to drought even low in grain yield. Meanwhile, upland rice lines of IR 75885-25-1-3-B-5-1-2-B-B, IR 75885-26-2-3-B-18-B-2- 1-B and Unsoed G19 resulted higher in grain yield under low dose of P than others. Unsoed G9 had both characters in efficient and respond to P, and drought tolerance with high in grain yield. Therefore, it needs to evaluate the performance consistency of both characters on those lines through grown under real conditions in the field of rainfed areas.